A New Method for Extracting and Measuring Methoxyfenozide Using ND/PAN-K10 SPE Using High Performance Liquid Chromatography - Marzieh Piryaei; Mir Mahdi Abolghasemi; Monireh Sobhi (Nanochemistry Research)
A sensitive, economical, and miniaturized self-assembly needle tip nanocomposite Polyaniline-K10 solid-phase microextraction (NDT/PAN-K10-SPNE) coupled with high-performance liquid chromatography UV detection was developed for rapid extraction removal and determination of methoxyfenozide in environmental water samples. The NDT/PAN-K10-SPE cartridge, assembled by packing 2.0 mg of PAN-K10 as sorbent into a needle tip, showed high adsorption capacity for methoxyfenozide owing to the large surface area and unique structure of PAN-K10. The factors that affected the extraction efficiency of PT-G-SPE, including sample volume, pH, sorbent amount, washing solvent and eluent solvent, were optimized. Good linearity for methoxyfenozide was obtained in a range of 0/01–100 µg mL−1 with the correlation coefficient of (R2) = 0.999. The recoveries of the methoxyfenozide at three spiked levels ranged from 84.72% to 100.03% with the relative standard deviations (RSD) of 3.78%. It is also noteworthy that the applied method is economical and has a good linear range, reproducibility, and high sensitivity.